Effects of deep and shallow water running on spinal shrinkage. Issue 1 (March 1998) - Dowzer, C N; Reilly, T; Cable, N T
Abstract : OBJECTIVES: Running in water has the potential to decrease the compressive forces on the spine as the body is supported. The aim of the study was to determine the magnitude of this loss in stature compared with running on land. METHODS: Fourteen runners completed three 30 minute runs on separate days in deep water, shallow water, and on a motor driven treadmill. During the three conditions, runners exercised at 80% of their exercise mode specific peak oxygen consumption. Subjects rested in the Fowler position for 20 minutes before and after exercise. Measurements of changes in stature were taken before resting, before running, after 15 minutes of running, after 30 minutes of running, and after the post-exercise rest in the Fowler position. Changes in stature were recorded using a stadiometer accurate to 0.01 mm. RESULTS: Loss of stature values were 4.59 (1.48), 5.51 (2.18), and 2.92 (1.7) mm (means (SD)) for running on the treadmill, and in shallow and deep water respectively. Running in deep water caused significantly lower creep than in the other trials (p<0.05), with no difference between the shallow water and treadmill conditions. Loss of stature was greater in the first half of the run for all conditions (p<0.05). Ratings of perceived exertion did not differ between the three exercise conditions. CONCLUSION: Results support the use of deep water running for decreasing the compressive load on the spine.